Evaluating Market Viability and Developing Digital Marketing Strategies for X-ray Detection Technology in Contemporary Security Environments - Sinaga, Hans Salomo Tiberias; Indradewa, Rhian; Nugroho, Sukmo Hadi; Kustiawan, Unggul (Bulletin of Management and Business, 2025)
The X-ray Screening System and other radiology-based diagnostic services are increasingly important for preventive and curative health care. This research will produce the Clinic X-ray Screening System's marketing business plan and examine market feasibility and digital customer acquisition tactics. STP analytical tools and NICE B2B Marketing Mix are used in the qualitative descriptive research. Literature studies, market observations, and diagnostic X-ray marketing data were used. Results demonstrate tremendous market penetration potential, notably in government, SOEs, business, hotels, and hospitals. The Indonesian X-ray screening system clinic marketing strategy must use data-driven techniques, IoT/AI technologies, and customized segmentation to solve operational and legal obstacles. To reach varied institutions, geographic, demographic, psychographic, and behavioral segmentation is essential, while digital marketing and strategic cooperation boost market legitimacy. Digitization (online bookings, digital outcomes), strategic collaborations, and fast, accurate service are effective marketing methods. This study offers healthcare business players realistic advice on developing technology-based diagnostic x-ray models